Analisis Interpretasi Ayat-Ayat Syukur dalam Tafsir Al-Misbah: Sebuah Pendekatan Psikologis - Utari, Rani; Masykurah, Siti; Alghifari, Abudzar (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2024)
This study aims to explore the psychological values contained in the Quranic verses related to the concept of gratitude, which, in Islamic teachings, is considered an important aspect in addressing various psychological issues. The study uses a library research method with a qualitative-descriptive approach, involving maudu’i analysis and content analysis to uncover the meanings of verses related to gratitude. The primary focus of this study is the interpretation of these verses in the Tafsir Al-Misbah, along with the integration of psychological literature to delve into the concept of gratitude in the context of modern psychology. The findings show that gratitude encompasses various psychological values, including positive emotions, mental health, psychological well-being, optimism, empathy, altruism, and prosocial behavior. These findings support McCullough’s theory, which highlights the positive impact of gratitude on mindset, mood, and behavior. The study concludes that the psychological values contained in gratitude play a significant role in the formation of individual psychological well-being and offer practical guidance on the application of gratitude in daily life. This research also contributes to connecting the Quranic religious perspective with modern psychology, expanding the understanding of the relevance of religion in supporting mental health.